Strategi Pemerintah Desa Dalam Mengembangkan Kampung Sabbeta Desa Pising Kecamatan Donri-Donri Kabupaten Soppeng - Ramdhana, Fitria; Usman, Jaelan; Mone, Ansyari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to determine the government's strategy in Developing Sabbeta, Pising Village, Donri-Donri District, Soppeng Regency. This study l used  qualitative research. Technique Collecting data used interviews, observations, and documentation. The  informants who involved in the development of Sabbeta Village. The data analyzed qualitatively. The results of this study indicated that 1) The strategy  cost advantage was not applied as a whole due to the silk production process requires a lot of costs, the differentiation strategy was applied through the creation of silk product innovations, and the focus strategy applied was to focus sales on the order system. 2) Several inhibiting factors in the development of the Village Sabbeta waw seen from the low quality of human resources and provision facilities and infrastructure were not really good . Keywords: government strategy, village development